Géomorphologie et processus expérimental - Cazalis, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1960)
For many years systematically concerned with the complementary disciplines of fundamental research and practical application, the science of geomorphology is now beginning to be removed from its classical purpose — the contribution to the understanding of geographical milieu — and to be extended to other more technical and non-geographical fields. Whether or not the new geomorphology remains in the academic ranks of geography, it is nonetheless necessary to redefine its methods, concepts, spirit, and in certain ways to abandon all empiricism, verbalism and apriority.Accordingly the science of geomorphology must be elaborated in terms of the general principles of experimental method and analytical process, the main lines of which, in epistemological perspective, are outlined here : trial and experimentation, inductive reasoning, experimental concepts.